Mapping Publication Trends of Problem-Based Learning in Visual Communication Design 2020–2025: A Google Scholar Bibliometric Analysis - Bt samsuddin, Yati (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to map research trends on Problem-Based Learning (PBL) in Visual Communication Design (VCD) during 2020–2025 through a Google Scholar–based bibliometric analysis. Bibliographic data were collected using Publish or Perish (PoP) with the query